Hydrogeological aspects of rock mechanics and mining subsidence around longwall extractions - Aston, Timothy Robert Colin (1982)
A problem of potential water occurrences exists, whenever coal reserves are worked beneath either surface or sub-surface water bodies. The object of this work is to examine hydrogeological techniques and problems which can be associated with longwall coal extraction.